Wire Electrical Discharge Machining (WEDM) optimization process: A conceptual view. Issue 1 (May 2020) - Zarith Rahmah Syed Ahmad, Sharifah; Mohd Zain, Azlan; Yusoff, Yusliza; Effiyana Ghazali, Nurzal; Zhou, Kai-Qing
Abstract: Optimization technique are solutions for finding for specific problems and solved existing limitation on common problems. This are especially in improving the output of WEDM processing where it involves more than a single objective or multiple output to be optimized synchronously. WEDM machining process usage increased rapidly as its capability in cutting complicated design formation. Thus the precision of the work piece is required. Therefore, this paper aims to provide a quick conceptual view of optimizing WEDM process by providing fundamentals parameters involved. Henceforth, perspective on WEDM optimization process on this paper may be use for future reference.